Interregional fiscal transfers resulting from central government debt: New insights and consequences for political economy - Geert Jennes (Kyklos, 2021)
The political geography of central government debt has hardly been investigated. We propose a method for calculating implicit interregional transfers stemming from central government debt. We apply this method to Belgium over the 1970-2016 period. The share of poorer Francophone Belgium in debt-financed central government spending was persistently larger than its share in central government revenue used to pay the resulting interest bills. The opposite holds for richer Flanders. Also, a primary deficit in one particular year leads to an interest bill in each of the following years as long as debt caused by that primary deficit is not repaid. All the above caused debt-related transfers from Flanders to Francophone Belgium of over 7% of Flemish GDP during many years. Interregional interest transfers may also be large in the many other democracies suffering from both high central government debt and considerable geographic income disparities. The size of these transfers may in turn explain the size and persistence of central government deficits. This is also because poorer, less densely populated regions such as Francophone Belgium tend to be overrepresented within central governments. This strengthens their ability to cause deficits. We recommend more fiscal decentralisation or at least smaller central government deficits.
Keywords: 300